Model rekabentuk bandar berasaskan bentuk bandar tradisional Melaka - Anwar, Markarius (2007)
Nowadays, the main challenge of new town is style of the urban design is not care about the identity, they are modern building that can be called as symbolizing of town development, otherwise it does not showing of heritage and local culture and not relevant with natural condition. Meanwhile, when we looking at old urban design in Malaysian, they have the uniqueness, such as architecture quality and attracted urban space, have been balancing of development stage with conservation of culture value, the suitable of natural condition, and have special characterization that forming image of place. Melaka of traditional town is one of old towns in Malaysia that have been uniqueness, so it is to be case study in this research. The main contribution of the research were the study formulation; The first is the base element of formulation that creates the urban physical, i.e., 1) morphology, 2) townscape and 3) urban structure. The second finding is methodology which relevant which this study i.e methodology of qualitative. The field observation is used for recording details of visual quality from characteristic of urban physical. The study analysis obtained secondary data that relevant with urban morphology. The third finding is the form of urban physical, the based on study of urban morphology. The fourth finding is quality of townscape depent of observation in the research site. The last finding is to proved the research objective, i.e. developing new model of urban design base on the traditional urban form. It is to get a relevant study toward the physical character of urban structure element, which are district, edge, pathways, nodes and landmark. Result of this research can be a design guidelines to develop a new town and can be used for next studies.